Phantom ex machina : digital disruption's role in business model transformation - Khare, Anshuman; Stewart, Brian; Schatz, Rod (Springer, 2017)
This book explores the factors that make digital disruption possible and the effects this has on existing business models. It takes a look at the industries that are most susceptible to disruption and highlights what executives can do to take advantage of disruption to re-invent their business model. It also examines the pivotal role that technology plays in creating new dynamics to business operations and forcing business model changes. Adoption of digital technology has caused process disruptions in a number of industries and led to new business models (e.g., Über, AirBnb) and new products. In addition to covering some of the more popular and well known examples, this book targets not so obvious disruptions in the education sector and in services and changing business models. Phantom Ex Machina: Digital Disruption's Role in Business Model Transformation is divided into six parts. The book begins with an introduction to digital disruption and why it matters. The next part of the book focuses on business strategy which includes case studies on the impact of social media and how digital disruption changes pricing strategies and price models. For part three, the authors observe technology's role in digital disruptions. Chapters cover how 3D printing is challenging existing business models and how the automotive industry is innovating with new perspectives. Part four covers higher education, recognizing digital disruption's transformation in graduate management education. Part five centers upon the service industry with a look at virtual teams and the emergence of virtual think tanks. Finally the book concludes with a look to the future, embracing disruptions.
Keywords: Information technology -- Economic aspects.; Technological innovations -- Economic aspects.; Success in business.; elektronické knihy; electronic books